Effects of metabolic syndrome on aortic pulse wave velocity. Issue 1 (December 2017) - Lee, Dong-Hyeon; Youn, Ho-Joong; Chung, Woo-Baek; Choi, Yun-Seok; Lee, Jong-Min; Park, Chul-Soo; Jung, Hae-Ok; Jeon, Hui-Kyung; Lee, Man-Young
Abstract Background The purpose of this study was to compare the value and evaluate the validity of non-invasive methods for the detection of vascular stiffness in never-treated individuals with metabolic syndrome (MetS). Methods A total of 59 subjects (mean age, 60 ± 12 years; male:female = 35:24) were enrolled in the study and were categorized into the positive MetS (MetS[+]:N  = 32) and negative group (MetS[−]:N  = 27), according to the parameters set by the National Cholesterol Education Program's Adult Treatment Panel III. Pulse wave velocity (PWV) of the aorta, arm, and leg, Framingham risk score (FRS), ankle-brachial index (ABI), and carotid intima-media thickness (IMT) for vascular aging were measured for the two groups. Results Aortic PWV (PWVaor ) was significantly higher in MetS(+) than MetS(−) group (7.0 ± 1.4 m/s vs. 8.4 ± 1.6 m/s, p  < 0.01), while ABI was significantly lower in MetS(+) than MetS(−) group (1.2 ± 0.1 vs. 1.1 ± 0.2, p  = 0.03), respectively. FRS was significantly higher in MetS(+) than MetS(−) group (11 ± 5 vs. 14 ± 4, p  = 0.05). The both mean IMT was higher in MetS(+) than MetS(−) group (right: 0.94 ± 0.20 mm vs. 0.81 ± 0.20 mm, p  = 0.03; left: 0.93 ± 0.20 mm vs. 0.79 ± 0.20 mm, p  = 0.03, respectively). For predicting the probability of the presence of MetS, PWVaor was an independent tool (p  = 0.04; odds ratio, 1.88; 95% confidence interval, 1.03 to 3.42) and a cut-off value of PWVaor of 7.4 m/s showed a sensitivity of 66.7% and a specificity of 47.6%. Conclusions We suggest that PWVaor, combined with traditional tools, can play an important role as a complementary or alternative tool for the detection of vascular stiffness in never-treated individuals with MetS.